The politics of soft law: progress and pitfall of the global compact for safe, orderly, and regular migration - Chetail, Vincent (Frontiers in Human Dynamics, 2023)
The Global Compact for Safe, Orderly and Regular Migration (GCM) epitomizes the potential and the limits of soft law in promoting global migration governance. While being a catalyst of multilateralism, the use of soft law remains highly ambiguous and must thus be approached with caution. At the same time, the GCM operates as a counter-narrative to populism insofar as it proposes a collaborative framework to develop global migration governance. Yet, its implementation record remains disappointing, and the last review carried out within the the UN General Assembly signals a return of realpolitik. This calls for a vigilant plea towards a principled implementation of the GCM with due regard to the commitments of states contained therein, as well as to their legal duties under international law. Following this stance, soft law and hard law are not mutually exclusive, but rather mutually reinforcing, provided they are implemented in a cogent and integrated way. The GCM can make a difference on the ground if, and only if, it works in tandem with legally binding norms and instruments. If not, it may eventually become nothing else than a mere smokescreen, if not a masquerade, for the patent violations of migrants' rights.